2019
DOI: 10.1111/and.13426
|View full text |Cite
|
Sign up to set email alerts
|

Salubrious effects of a vermiculite–cellulose‐based bionanocomposite on oxidative stress indices and histomorphology of male Wistar rats

Abstract: There is a current interest from the food packaging, biomedical and agricultural sectors in hybrid materials formed from clays and natural polymeric compounds. However, research investigating the toxicity of vermiculite–cellulose nanocrystal (VERN) hybrid on the testes of Wistar rats is rare. Twenty rats, divided into control and treatment groups, were orally administered distilled water, 5, 10, and 20 mg/kg bw VERN daily for two consecutive weeks. At the termination of experiments, the testicular organo‐somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In the current study, rats administered with GSC showed differential effects on testicular and epididymal antioxidant enzymes, except CAT. GSC, at all treatment doses, did not disturb CAT activity in both testis and epididymis, lending credence to earlier reports that this enzyme may have limited importance in male reproductive organs [ 7 , 31 ]. In the testis, SOD activity remained unchanged, while epididymal SOD activity decreased at the high dose GSC treatment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the current study, rats administered with GSC showed differential effects on testicular and epididymal antioxidant enzymes, except CAT. GSC, at all treatment doses, did not disturb CAT activity in both testis and epididymis, lending credence to earlier reports that this enzyme may have limited importance in male reproductive organs [ 7 , 31 ]. In the testis, SOD activity remained unchanged, while epididymal SOD activity decreased at the high dose GSC treatment.…”
Section: Discussionsupporting
confidence: 86%
“…The diverse applications of cellulose add another level of complexity arising from increased human exposure; therefore, there is an obligation to assess the health implications of exposure to cellulose. We have chosen the male reproductive organs as the target organs of toxicity following our previous study showing the slight testicular-toxicity of cellulose bionanocomposite [ 7 ]. Data obtained from this study indicated that GSC treatment in rats did not elicit changes on absolute weights and organosomatic indices of both testis and epididymis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation